Synthesis and characterization of graft and block copolymers using hydroboration - Baleg, Abd-Almonam (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2006.